1996
DOI: 10.1021/om960416e
|View full text |Cite
|
Sign up to set email alerts
|

Dicationic Nickel(II) Carbonyl Complexes Containing Tetradentate Ligands

Abstract: This article describes the preparation and spectroscopic characterization of three dicationic Ni(II) carbonyl complexes containing tripodal tetradentate ligands. An X-ray diffraction study of [Ni(PP 3 E)(CO)](BF 4 ) 2 (where PP 3 E is tris(2-(diethylphosphino)ethyl)phosphine) has been completed and confirms a trigonal bipyramidal structure with an apical carbonyl ligand. The binding of CO is weak and reversible. The stability of these complexes is enhanced by the small chelate bite imposed by the tetradentate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…The Ni-C distance refined to 1.78(2) Å, and the Ni-O distance refined to 2.90(2) Å, leading to a C-O bond length of 1.12(4) Å. Although this is short for a C-O bond, it is not without precedent for Ni-CO complexes (57)(58)(59)(60) and indicates that the CO is approximately linear and a terminal ligand of the Ni center.…”
Section: Resultsmentioning
confidence: 97%
“…The Ni-C distance refined to 1.78(2) Å, and the Ni-O distance refined to 2.90(2) Å, leading to a C-O bond length of 1.12(4) Å. Although this is short for a C-O bond, it is not without precedent for Ni-CO complexes (57)(58)(59)(60) and indicates that the CO is approximately linear and a terminal ligand of the Ni center.…”
Section: Resultsmentioning
confidence: 97%
“…Bearing in mind that not many Ni II ‐CO complexes are known to date, [25, 28–39] due to the limited ability of Ni II to stabilize such entities via backbonding, we next tested whether a Ni II ‐CO complex with the L t Bu− ligand system would be stable at all and reacted the cationic complex [L t Bu Ni II (OH 2 )][B(Ar F ) 4 ] ( 2 , see S3) with CO gas. A change of color from green to purple could be observed, and evaporation of all volatiles left behind a purple solid.…”
Section: Resultsmentioning
confidence: 99%
“…Bearing in mind that not many Ni II -CO complexes are known to date, [25,[28][29][30][31][32][33][34][35][36][37][38][39] due to the limited ability of Ni II to stabilize such entities via backbonding,w en ext tested whether aN i II -CO complex with the L tBuÀ ligand system would be stable at all and reacted the cationic complex (Figure 2). Thestructure determination further revealed that one of the aryl rings of L tBu undergoes an h 2 coordination, thus completing as quare planar coordination sphere of the Ni center,w hich also reflects in ad iamagnetic 1 HNMR spectrum of as olution of 3 in CD 2 Cl 2 .…”
Section: à -Liberation Of Comentioning
confidence: 99%
“…Most of these complexes are five‐coordinate, an observation that has been theoretically justified in terms of a more efficient π back‐donation from the Ni II center to the CO ligand 37. In fact, five‐coordinate nickel monocarbonyl derivatives containing the CO ligand in either axial or equatorial positions, show low‐frequency ν (CO) values as for instance in ( TBPY ‐5‐23)‐[NiI 2 (CO)(fdma)] (fdma=ferrocene‐1,1′‐bis(dimethylarsine); ν (CO)=2054 cm −1 ),38 ( TBPY ‐5‐22)‐[NiI 2 (CO)(PMe 3 ) 2 ] ( ν (CO)=2015 cm −1 )31 and ( TBPY ‐5‐13)‐[Ni(PP 3 E)(CO)] 2+ (PP 3 E=tris{2‐(diethylphosphino)ethyl}phosphine; ν (CO)=2050 cm −1 ) 39. Even in the tricarbonyl derivative ( TBPY ‐5‐11)‐[Ni(SiCl 3 ) 2 (CO) 3 ], the ν (CO) absorption appears at 2079 cm −1 33.…”
Section: Resultsmentioning
confidence: 99%